Glutathione‐S‐transferase P1 may predispose children to a decline in pulmonary function after stem cell transplant. Issue 7 (2nd February 2017) - Stark, Julie; Renbarger, Jamie; Slaven, James; Yu, Zhangsheng; Then, Jenny; Skiles, Jodi; Davis, Stephanie
Abstract: RATIONALE: Pulmonary complications after hematopoietic stem cell transplant (SCT) are associated with increased mortality. Genetic markers for those at risk for pulmonary impairment post‐SCT have not been widely investigated. METHODS: Forty‐nine patients were retrospectively selected from a single institution's biorepository with linked clinical data. All subjects performed pre‐SCT PFTs. Genotyping was conducted using the Infinium Exome‐24 BeadChip. Four single nucleotide polymorphisms (SNPs) were selected (rs1800871, rs1695, rs1800629, rs12477314) and evaluated for association with PFT parameters as change over time from baseline. Associations between SNPs and PFT parameters were assessed and adjusted for the following confounding variables: age, gender, and race. RESULTS: Using the recessive genetic model, patients with one or two minor alleles for the glutathione S‐transferase P1 ( GSTP1 ) SNP rs1695 had a lower decline in FEV1 and FEF25‐75 at 1‐year post‐SCT compared to patients who were homozygous for the ancestral allele (adjusted P ‐values <0.01 and 0.02, respectively). No other SNPs were significantly associated with other PFT parameters. CONCLUSIONS: Our findings suggest that GSTP1 genotype may be associated with lung function during the first year post‐SCT. Identifying and investigating genes that predispose patients to pulmonary complications after SCT may allow for more personalized patient management based on pre‐emptive genetic testing. The glutathione S‐transferase gene merits further investigation.